Fantastic beasts : 3-film collection [videorecording (Blu-Ray)] - Redmayne, Eddie, 1982-; Waterston, Katherine; Fogler, Dan; Sudol, Alison, 1984-; Depp, Johnny; Law, Jude, 1972-; Miller, Ezra; Farrell, Colin, 1976-; Kravitz, Zoë, 1988-; Ejogo, Carmen, 1974-; Kim, Claudia, 1985-; Guthrie, Kevin, 1988-; et al. (Warner Bros. Entertainment Inc., 2020)
Fantastic beasts and where to find them: It opens in 1926 as Newt Scamander has just completed a global excursion to find and document an extraordinary array of magical creatures. Arriving in New York for a brief stopover, he might have come and gone without incident, were it not for a No-Maj (American for Muggle) named Jacob, a misplaced magical case, and the escape of some of Newt's fantastic beasts, which could spell trouble for both the wizarding and No-Maj worlds.